Pemberdayaan Ekonomi Masyarakat Melalui Wakaf Produktif (Studi Kasus di Kecamatan Maritengngae, Kabupaten Sidenreng Rappang) - Aldi R, Maulana Yusup; Hasibuddin, M.; Baedah, Said Syarifuddin Abu; Akil, M. (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The purpose of this research is to find out, examine how productive waqf management for community economic empowerment in Maritengnge District, Sidenreng Rappang Regency. This is defined as something that is systematic and structured which utilizes waqf assets which are then used for the benefit of the people. Especially in Maritengngae District, Sidenreng Rappang Regency. The data was collected through observations, interviews, and documentation from related parties such as waqf, nadzir, and mauquf alaih. The result of this research shows the authenticity of nadzir in managing productive waqf for community economic empowerment in Maritengngae District, Sidenreng Rappang Regency. Although there are inhibiting and supporting factors in the management, the role of nadzir can overcome this with the legitimacy and transparency of the development of waqf asset management. The results of this study reveal the significant success of waqf asset management in Maritengngae District, Sidenreng Rappang Regency. Which prioritizes the development of human resources in the form of schools, boarding schools, and mosques.